The treatment of Covid tongue in an isolation unit - Dwi Setianingtyas; N. Nafiah; Cane Lukisari; Paulus Budi Teguh; Felicia Eda Haryanto; Erni Marlina (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: In 2019, a viral disease spread from Wuhan, Hubei Province in China. The disease was caused by severe acute respiratory syndrome related to coronavirus 2 (SARS-CoV-2 virus), which was named by the Coronavirus Study Group of the International Committee on Taxonomy of Viruses. Purpose: This article reports the multi-discipline treatment of Covid tongue and exfoliative cheilitis with a main diagnosis of bilateral pneumonia caused by SARS-CoV-2 infection. Case: A female patient, 70 years old was referred with a diagnosis of bilateral pneumonia by a pulmonologist. She complained of painful wounds all over her mouth. An intraoral clinical examination revealed white-thick lesion and multiple ulcerations, whilst an extraoral exam for exfoliative dermatitis has not been described. The working diagnosis was Covid tongue mixed with exfoliative cheilitis. Case management: The procedure was performed by teledentistry and direct visits to implement oral health care by asepsis, debridement and the application of Oxygene gel. Conclusion: The lesion was treated successfully due to the multidisciplinary approaches by an internist and pulmonologist by implementing integrated knowledge and was supported hugely by patient cooperation.